NEGLECTED CONGENITAL MUSCULAR TORTICOLLIS TREATED WITH BIPOLAR RELEASE: A CASE REPORT AND OVERVIEW - Kitta, Muhammad Ihsan (JIKI Jurnal Ilmiah Kesehatan IQRA, 2019)
Introduction Torticollis a symptom of cervical spine abnormality. The most common form of congenital painless torticollis is congenital muscular torticollis (CMT), or wry neck. This is a case of neglected congenital muscular torticollis treated by bipolar sternocleidomastoid (SCM) muscle release at the age of 12 years followed by active physiotherapy and exercises. Case report A 12-year-old girl affected with neglected congenital muscular torticollis involving the left SCM with no evidence of cervical vertebra abnormalities besides the increased cervicomandibular angle. A treatment plan of bipolar surgical release of the left SCM was formulated, followed by postoperative utilization of a cervical brace, aggressive physical therapy along with postural exercises. Functional and cosmetic result was excellent with improved cervical range of motion and centered head position. At 4 months postoperative, patient was able to extend the neck and perform rotation to the opposite site and there was only a moderate amount of scar tissue formed at the surgical site. Radiographic examination also revealed excellent postoperative CMA value. Discussion CMT has an unclear aetiology although it is postulated that foetal position abnormalities, intrauterine or perinatal compartment syndrome and birth trauma ensuing a difficulty delivery embody the main causes. The main approach to the condition remains a trial of conservative treatment consisting of stretching manoeuvres, although surgical release of the affected SCM is recommended for resistant cases. Manual stretching is most effective if performed before the age of 12 months. This stretching technique can also be combined with Botulinum toxin A injections. Surgery itself is highly recommended when a restriction of movement up to thirty degrees is present, as well in cases complicated with deformities of facial bones. Conclusion No clear consensus regarding which surgical technique provides the best chance at restoring a near normal function and cosmesis for neglected cases of CMT.